The design of professional qualification model for the tourism marketing with the goal for sustainable development (Czech Journal of Multidisciplinary Innovations, 2024)
Background and purpose summary: Considering the lack of theoretical studies in the field of what is the competence of tourism marketing professions, in this article, a reflective and future-research study on the competence of tourism marketing professions with a view on sustainable development has been discussed. Methodology: The required data were collected from two parts of the research literature in order to identify the indicators of professional competence (marketing) of tourism, as well as the opinions of 9 senior managers of government organizations and reputable tourism companies to identify the local structure of the indicators. In order to identify the indicators, the inductive content analysis tool was used, and in order to present the native model, the theme analysis tool was used in the Max QDA software.